2002
DOI: 10.1124/dmd.30.12.1368
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Kinetics for the Formation of 3-Hydroxyquinine and Three New Metabolites of Quinine in Vitro; 3-Hydroxylation by CYP3A4 is Indeed the Major Metabolic Pathway

Abstract: ABSTRACT:The formation kinetics of 3-hydroxyquinine, 2-quininone, (10S)-11-dihydroxydihydroquinine, and (10R)-11-dihydroxydihydroquinine were investigated in human liver microsomes and in human recombinant-expressed CYP3A4. The inhibition profile was studied by the use of different concentrations of ketoconazole, troleandomycin, and fluvoxamine. In addition, formation rates of the metabolites were correlated to different enzyme probe activities of CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4 in microsomes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Inhibition experiments were carried out using 1 μ m ketoconazole, 100 μ m troleandomycin, 10 μ m clopidogrel, 5 μ m sulfaphenazole or 25 μ m quercetin. High inhibitor concentrations were chosen according to the literature because inhibitors have not been extensively evaluated for the horse yet (Newton et al ., ; Li et al ., ; Mirghani et al ., ; Richter et al ., ; Sanchez et al ., ; Ghosal et al ., ; Polasek & Miners, ; Nebot et al ., ; Greenblatt et al ., ). Inhibitors were pre‐incubated for 30 min prior to addition of 100 μ m TES in order to account for possible mechanism‐based inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition experiments were carried out using 1 μ m ketoconazole, 100 μ m troleandomycin, 10 μ m clopidogrel, 5 μ m sulfaphenazole or 25 μ m quercetin. High inhibitor concentrations were chosen according to the literature because inhibitors have not been extensively evaluated for the horse yet (Newton et al ., ; Li et al ., ; Mirghani et al ., ; Richter et al ., ; Sanchez et al ., ; Ghosal et al ., ; Polasek & Miners, ; Nebot et al ., ; Greenblatt et al ., ). Inhibitors were pre‐incubated for 30 min prior to addition of 100 μ m TES in order to account for possible mechanism‐based inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…The 8‐hour urinary ratio of debrisoquin/4‐hydroxydebrisoquin was used as the phenotype measure of CYP2D6 activity 28 . The activity of CYP3A4 was estimated by the hydroxylation of quinine to the 3‐hydroxy metabolite in a 16‐hour plasma sample 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…We measure CYP3A4 activity indirectly through the exogenously administered probe drug quinine [17], which is primarily metabolized by CYP3A4 -and to a lesser extent by CYP3A5 -into 3-hydroxy quinine [18,19]. Previous studies have shown that quinine 3-hydroxylation reaction measured in plasma and urine samples in humans is a stable measure of baseline and induced CYP3A4 activity [20][21][22].…”
Section: Biochemical Assays Of Cyp3a4 Enzyme Activitymentioning
confidence: 99%